Effect of cesium chloride modification on the film morphology and UV-induced stability of planar perovskite solar cells. Issue 30 (16th December 2015) - Li, Wenzhe; Li, Jiangwei; Niu, Guangda; Wang, Liduo
Abstract : The interface modification of perovskite thin films has shown great potential to boost the performance of perovskite solar cells during the last few years. Abstract : The interface modification of perovskite thin films has shown great potential to boost the performance of perovskite solar cells during the last few years. Here we demonstrate that cesium chloride (CsCl) as crystal seeds can markedly enhance the coverage of the CH3 NH3 PbI3− x Cl x absorber layer on TiO2 in planar heterojunction solar cells, thus boosting the power conversion efficiency (PCE) to 16.8%, with a fill factor (FF) of 0.79. Also, the introduction of CsCl significantly improved the stability of CH3 NH3 PbI3− x Cl x under ultra violet (UV) irradiation, which has been verified by XRD, XPS and SEM measurements. The CsCl-treated devices maintained 70% of the original PCE after a prolonged intensive UV irradiation of 200 min while the untreated devices being almost exhausted. Furthermore, we proposed the mechanism concerning CsCl as the modification layer to improve the UV-induced stability issue of perovskite solar cells.